Design of Prestressed Cable Dome Using Minor Perturbation Method - Haitao Zhou; Feng Fu; Bo Si; Deqing You; Fengjian Zhang (Buildings)
For the structural design of cable domes, the determination of prestress force distribution, the section of the structural components, and initial configuration are prerequisites for the subsequent detailed design of cable and strut sizes. To solve this problem, this paper elucidates the basic theory of the Minor Perturbation Method, introduces this theory into the field of force finding design for cable dome structures, and develops a new design method whose core is the comparison between the combined stress of each component conforming to mechanical characteristics of cable-strut structure and control stress, and meeting the convergence condition by adjusting the prestress level and cross-section of components. A corresponding design flow chart is established and programmed with finite element analysis software. Through the case studies of two different kinds of cable dome, it is proven that the proposed method and software program can simply, quickly, and effectively design the cable domes with an economic cross-section.